2021
DOI: 10.1055/a-1479-2199
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after EUS-guided radiofrequency ablation: Prospective results in pancreatic neuroendocrine tumors and pancreatic cystic neoplasms

Abstract: Background and study aims Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) for pancreatic neuroendocrine tumors (NETs) and intraductal pancreatic mucinous neoplasia (IPMN) with worrisome features or high-risk stigmata (WF/HRS) has been evaluated in few series with short-term outcomes. This studyʼs primary endpoint was to assess the long-term efficacy of EUS-RFA in patients with NETs or pancreatic cystic neoplasms (PCNs) over at least 3 years. Patients and methods Twelve patients had 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Regardless of the good agreement between investigators in terms of tumor diameter, there was also perfect agreement with regard to the antitumor effect noted in the gene therapy trial by the principal investigator 6 . Although the effect was modest and is currently being assessed on a larger scale during the Phase 2 study (Thergap-2 trial), this method is indicative of an important area of investigation in line with the EUS-guided administration of local antitumor treatments such as gene therapy, radiofrequency, and chemotherapy 6 15 16 17 18 . A centralized system, therefore, can be established for future protocols, provided that a clearly defined, standardized EUS recording is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the good agreement between investigators in terms of tumor diameter, there was also perfect agreement with regard to the antitumor effect noted in the gene therapy trial by the principal investigator 6 . Although the effect was modest and is currently being assessed on a larger scale during the Phase 2 study (Thergap-2 trial), this method is indicative of an important area of investigation in line with the EUS-guided administration of local antitumor treatments such as gene therapy, radiofrequency, and chemotherapy 6 15 16 17 18 . A centralized system, therefore, can be established for future protocols, provided that a clearly defined, standardized EUS recording is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…They found that 12 of 14 lesions completely disappeared, although 2 failures were noted. One was a recurrence after the initial disappearance of the lesion after one year, and the second involved no initial response to the treatment and development of metastases [49]. The overall complication rate was 13.79%, and complications were pancreatitis, perforation in a patient with a cystic lesion, one biliary leakage, and pancreatic duct stenosis.…”
Section: Reviewmentioning
confidence: 98%
“…Radiofrequency ablation relies on delivery of a high-frequency alternating current through a needle or needle-like device, which heats the tissue and triggers tumour necrosis [46,47]. The reports describe the effectiveness of radiofrequency ablation in different types of tumours including hepatocellular carcinoma, well-differentiated thyroid, and medullary cancer [48], and different types of pancreatic tumours, including cystic neoplasms and cancer [49,50]. Current experience with EUS-guided radiofrequency ablation of NF-pNETs is limited mainly to case reports and series [51][52][53].…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, studies on EUS-radiofrequency ablation of mural nodules within IPMNs recently reported inspiring results with 100 % effectiveness [7]. However, long-term follow-up (3 years) of these patients resulted in up to 12 % incidence of pancreatic cancer [8].…”
mentioning
confidence: 99%